Challenges And Developments Of Islamic Banking In Indonesia - Muhammad Irgi Perdana; Dhea Indriati Sihaloho; Silmi Humaira Harahap; Cinta Nikita Aulia; Meigia Nidya Sari (CV. AFDIFAL MAJU BERKAH, 2025)
The purpose of this study is to examine the difficulties facing Indonesia's Islamic banking industry as it develops. With the combination of three Indonesian Islamic banks to form Bank Syariah Indonesia, a significant force, Islamic banking in Indonesia has grown and developed. Despite this, the Indonesian Islamic banking industry still faces several obstacles. Using secondary data from the Financial Services Authority, Bank Indonesia, Law No. 21 of 2008 regulating Sharia Banking, and other papers pertaining to Islamic banking in Indonesia, this study employs a library research methodology. This study identifies a number of issues that need to be resolved in order to boost Islamic banking's expansion and sustain its acceleration. The first issue is that Indonesian Islamic banking does not adequately utilize both the quantity and quality of human resources. Second, the low degree of public awareness regarding Islamic financial institutions in Indonesia and the creation of Islamic banking goods and services that are seen as less creative and competitive than those of other conventional banks. Third, it is also thought that the religious court system is insufficient to settle disagreements over Islamic financial transactions. Fourth, there are discrepancies and nationally and globally. disagreements in the alignment of items due to the various nations' varying interpretations of madhhab in fiqh muamalah.